The Relationship Between Nurses' Caring Behavior And The Level Of Spirituality Of Patients In The Lidwina And Yosef Hospital Rooms Santa Elisabeth Medan: Caring Behavior And The Level Of Spirituality - Enni Lidia Pasaribu; Karo, Mestiana; Siallagan, Ance M. (STIKes Mandala Waluya Kendari, 2024)
Background: Spirituality is one of the things that affects the health of patients, unmet spiritual needs will make patients unable to overcome their health problems, and can even slow down the healing process in these patients. The purpose of this study was to analyze the relationship between nurses' caring behavior and the level of spirituality of patients in the Lidwina and Yosef rooms of Santa Elisabeth Hospital Medan in 2023. Methods: This study used a cross sectional design. Sampling using purposive sampling technique with a total sample size of 60 respondents. The instruments used in this study were caring behavior questionnaire and DSES. Results: The results showed that the majority of nurses' caring behavior was in the excellent category as many as 50 respondents (83%) and the majority of patients' spirituality level was in the high category as many as 58 respondents (97%). Conclusions: Based on the Spearman rank statistical test, the p-value is 0.000 (p <0.05) with a correlation index of 0.547. This means that there is a moderate and positive relationship (unidirectional) between the caring behavior of nurses and the spirituality of patients in the Lidwina and Joseph rooms of Santa Elisabeth Hospital Medan in 2023. It is expected that nurses can improve and maintain the level of spirituality of patients through caring behavior and empathy provided by nurses.